PENGARUH MARJIN LABA BERSIH DAN PENGEMBALIAN ATAS EKUITAS TERHADAP HARGA SAHAM PERUSAHAAN INDUSTRI BARANG KONSUMSI - Rahmadhani, Sari Nuzullina (Universitas Medan Area, 2019)
This research aims to detemine the effect of net profit margin and return on equity to the stock price on consumer goods industry listed on the Indonesia Stock Exchange. Independent Variables are net profit margin and return on equity. Dependent Variable is stock price. The population in this research are all consumer goods industries listed on the Indonesia Stock Exchange during the period 2012 to 2016 as much as 37companies.The type of this research is associative causal. The sampling technique was purposive sampling, which is based on certain criteria and got as much as 22 companies. The analysis used classic assumption testing, hypothesis testing, and linear regression. The results show that net profit margin and return on equity have positive effect and significant on stock price for simultaneous. And for partial, net profit margin has positive effect on stock price and return on equityhas positive and significant on stock price.